2021
DOI: 10.35631/jistm.622014
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Survey Study on the Reception of Indoor Hydroponics System for Low-Income Household in Selangor

Abstract: Indoor hydroponics system is gaining acceptance and traction in providing practical indoor farming capabilities for urban dwellers, including in low income housing estates. However, for the low income urban dwellers, the size of their residence might restrict the design of the indoor hydroponics system, especially in terms of available floor space. Furthermore, before one starts to develop an indoor hydroponics system, it is imperative to identify users’ preferences, in terms of the types of plants to grow, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, for the latter, the available home space may restrict the design of the hydroponic system. As for user preferences, in terms of the types of plants to grow, price, and design, more studies are needed to allow researchers to develop a system that best suits the average citizen [101].…”
Section: Food System Sustainability Problem Home Hydroponics Solution...mentioning
confidence: 99%
“…However, for the latter, the available home space may restrict the design of the hydroponic system. As for user preferences, in terms of the types of plants to grow, price, and design, more studies are needed to allow researchers to develop a system that best suits the average citizen [101].…”
Section: Food System Sustainability Problem Home Hydroponics Solution...mentioning
confidence: 99%
“…Moreover, hydroponic systems require as little as 10% of the water used for traditional agriculture (Taylor et al, 2012) and produce higher yields with less labour inputs than soil-based farming (Astee & Kishnani, 2010). However, the substantial initial investment required for hydroponics remains a major obstacle to widespread adoption in the region (Wood et al, 2020), as seen in Selangor, Malaysia, where that cost was identified as the primary deterrent to residents' willingness to engage in this practice (Hamdan et al, 2021). Meanwhile, in Singapore, the limited availability of technical training, installation support, and incentives has hindered broader adoption of hydroponics (Wong et al, 2010), while in Kuala Lumpur, the extent of participation in hydroponics was linked to people's confidence levels and satisfaction with the practice (Ahimaz et al, 2021).…”
Section: Rooftop Gardeners In Asiamentioning
confidence: 99%
“… Notable exceptions include work by Ahimaz et al (2021), Hamdan et al (2021), and Hamzah et al (2016) in Malaysia and and Pham Thi Minh Khuyen (2019) and Pham and Turner (2020) in small Vietnamese cities.…”
mentioning
confidence: 99%